2021
DOI: 10.1002/cssc.202002748
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐Efficient Synthesis and High Thermoelectric Performance of α‐Cu2−ySe1−xTex

Abstract: The high‐temperature phase of β‐Cu2Se always appears as the major phase for the reaction carried out using chemical solution methods. Here, a procedure was developed that could fabricate a single phase of α‐Cu2Se1−xTex (x=0.02 and 0.04) by room‐temperature aqueous synthesis using NaBH4 as reducing agent followed by cold pressing and sintering at 650 °C for 6 h in a flowing gas mixture of 20 % H2 and 80 % N2. The energy‐efficient synthesis carried out at room temperature abides by the 6th principle for green ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…6b). 20,[31][32][33][34]39,40 In the Te contents range from x ¼ 0.2 to 0.3, we found that the transition phase point at Te of 0.25 achieved the highest ZT value, compared with other Te contents. K. Zhao et al investigated the thermoelectric © 2022 The Author(s).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…6b). 20,[31][32][33][34]39,40 In the Te contents range from x ¼ 0.2 to 0.3, we found that the transition phase point at Te of 0.25 achieved the highest ZT value, compared with other Te contents. K. Zhao et al investigated the thermoelectric © 2022 The Author(s).…”
Section: Resultsmentioning
confidence: 71%
“…6b). 20,31–34,39,40 In the Te contents range from x = 0.2 to 0.3, we found that the transition phase point at Te of 0.25 achieved the highest ZT value, compared with other Te contents. K. Zhao et al investigated the thermoelectric properties of Cu 2 Se 1− x Te x ( x = 0 to 1) solid solutions and they found the highest ZT value with x = 0.3 but the series of samples of x = 0.25 was missed.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The total thermal conductivity is composed of electronic and lattice thermal conductivities, κ e and κ L , respectively. 2 For a TE material to be considered good, it should have high electrical conductivity, large thermopower, and low thermal conductivity, which are interrelated, making the optimization of parameters essential. In the past, doping, 2 alloying, 3 and band engineering 4 were used to enhance the electronic transport properties of TE materials.…”
Section: Introductionmentioning
confidence: 99%
“…A thermoelectric device is a technology that can directly convert heat energy into electrical energy [1], [2]. In principle, this technology uses a material that can collect thermal energy and convert it into electrical energy [1]- [4].…”
Section: Introductionmentioning
confidence: 99%